Airport Passenger Experience Model For Terminal Low-Cost Carrier (Study Case at Terminal 1 Soekarno–Hatta International Airport) - Yolanda Sagala, Mora; Primiana Sagir, Ina; Chaerudin, Iman (Cv. Syntax Corporation Indonesia, 2021)
Introduction : The high traffic of flight movements and the number of airport passengers around the world are placed in very high demands on the airport industry business. For example the airport operator PT. Angkasa Pura II (Persero) or AP II is trusted to manage 19 airports and airport-related services to concentrate their service business on customers (Customer Centric Organization). Objective : This study aims to obtain the Airport Passenger Experience Model in Terminal 1 of Soekarno-Hatta International Airport as a Low-Cost Carrier Terminal. Development of a passenger activity service model to address the gap between the level of importance and service perceived by business and leisure passenger types at all travel touch points in service processing activities and non-processing activities. Method : This study uses 50 service attributes and 100 samples of respondents. The questionnaires were distributed twice. The first questionnaire uses the Quality Function Deployment (QFD) method to determine the performance of each service attribute through identification of passenger needs and desires (Needs). The second questionnaire uses the Analytic Hierarchy Process (AHP) to obtain a ranking or priority order based on the level of importance of airport passengers (Importance). Results : The results of the formulation of the House of Quality (HoQ) from a combination of QFD and AHP analysis methods get 5 priority programs (Panca Programs) from 17 Needs & Importance technical responses, including Customer Centric, Strategic Approach to Customer Service, Innovative, Sense of Place and Positive Ambiance. These have been adapted to the types of business passengers and leisure passengers at Terminal 1 Soekarno-Hatta Airport as a template for the Airport Passenger Experience Model for Low-Cost Carrier Terminals. If the manager of Terminal 1-BSH can carry out the five priority technical responses, then it can meet the needs of airport passengers by contributing 53.73% and if the sixth to tenth priority technical response is also carried out, it will increase the airport passenger experience by contributing as much as 84.80% as optimization of airport service performance at Terminal 1 Soekarno-Hatta Airport. Conclusion : Based on the identification of the needs and expectations of Terminal 1 - BSH passengers through the Quality Function Deployment (QFD) method, there are 20 service attributes that have a negative gap value or exceed the average satisfaction threshold. Out of the 50 indicators of passenger activity service processing, it shows that airport passengers are still dissatisfied with the services provided or there is a decrease in the quality-of-service performance. The proportion of passengers’ dissatisfaction in the departure service area is higher than in the arrival area.